Perception of Awareness on Attractive Appearance Through Industrial Work Practices as an Indicator of Employability Skills - Oot Khotijah (Syntax Corporation Indonesia, 2021)
e research objective was to analyze the perceptions of students, teachers, and business advisers about the awareness of appearing attractive as an indicator of employability skills in the marketing profession. The study population was students of SMK Negeri in Cilacap Regency, Online Business and Marketing Competence. The sample is determined proportionally by the class rank of 20 students. Data collection was carried out by means of observation, interviews and documentation. Meanwhile, data analysis was carried out using thematic analysis with the aim of identifying patterns of themes. The thematic analysis stage includes: (1) familiarizing oneself with the data; (2) generate the initial code; (3) search for themes; (4) review the theme; (5) define and name themes; and (6) producing reports.The results of the study: (1) perceptions of students, teachers and business advisers about the awareness of performing attractive contributions to employability skills; (2) the continuity of topics and themes that are built on the awareness of appearing attractive contributes to employability skills in the marketing profession, (3) differences in perceptions of the three respondents lead to the role of respondents regarding the relationship between awareness to appear attractive still with the character building of employability skills in the marketing profession. (4) the relationship between the employability skills that appears in the form of perceptions which refers to the characteristics of the characteristics of awareness that appear attractive to the marketing profession.